ONE HADITH ONE PRESENTATION AS A HADITH LITERACY MODEL IN A MODERN PESANTREN - Istifarin, Nur Annisa; Idri, Idri (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Hadith learning in traditional Islamic boarding schools (pesantren) tends to rely on the sorogan and bandongan methods. While these have limitations in developing students' critical analysis skills and digital literacy. IBS PKMKK addresses this challenge through the One Hadith One Presentation program, which integrates traditional approaches with modern learning methods. This study aims to analyze the implementation of the One Hadith One Presentation program at IBS PKMKK, focusing on the curriculum design, the resulting learning model, and its contribution to strengthening students' hadith literacy competence. The research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with the IBS PKMKK leadership and teaching staff, and documentation studies. The findings indicate that this program not only enhances students' comprehensive understanding of hadith but also provides a distinct learning experience, strengthens academic literacy skills, trains scientific communication skills, and facilitates the integrative character building of the students. Overall, the One Hadith One Presentation program can be an effective, integrative, and relevant model for hadith learning in the context of modern pesantren. The program successfully developed an integrative hadith learning model through seven educational pillars, encompassing digital presentation activities, creative visualization, and thematic studies. The program represents an effective pedagogical innovation in transforming hadith learning from a memorization-based approach towards independent knowledge construction. It not only strengthens students' multiliteracy competencies but also serves as a model for the convergence between pesantren traditions and the demands of modern education.